Risks of the future’s (digital) city: control, ghettoization and rootlessness (Andamios, Revista de Investigación Social, 2017)
This paper tries to claim the problem concerning the digital interrelation tools in order to make a theoretical approximation to the urban spaces. In this sense, we try to make some questions on the roots and rootlessness in a city mediated by digital technology. On the one hand, digital ground drives us towards a configuration of micro-spaces of inmunity and towards a security space of control as well. On the other hand, the saturation of interpellations and stimuli entails the paroxistic acceleration in our digital and urban lives. At the junction between digital urbs, civitas  and polis , it is a must a critical reflexion on the way we would like to live in the tomorrows’ city.
Keywords: Digital city; sociology of time; security culture; philosophy of technology; media sociology